Physical Activity and Body Composition Profiles in Elderly Individuals: Insights from a Community-Based Study - Sayisvir, Nadia Farah; Kurniati, Ardesy Melizah; Santoso, Budi; Husin, Syarif; Amalia, Ella; Izzulhaq, Muhammad Agung (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. Obesity and sarcopenia are two metabolic disorders that can result from an increase in body fat and a reduction in muscle mass that are not balanced by enough physical exercise. The goal of this study was to examine whether there is a link between physical activity and body composition in the elderly. Methods. This cross-sectional study was carried out in the elderly community of RSUP Dr. Mohammad Hoesin Palembang from October to November 2019. The study's sample consisted of older persons over the age of 60 who were able to speak clearly and carry out daily tasks independently. Respondents who agreed to participate signed informed consent. Physical activity data were collected by PASE questionnaire interviews, and body composition was measured using the BIA Tanita. Results. The Chi-Square test was used in all analyses. In this study, there were 94 old people: 12 men and 82 women. Physical activity was found to have a significant link with muscle mass (p=0,001) as well as fat mass (p=0,001). Conclusion. There is a strong link between physical activity and body composition in the elderly. Physical activity data were obtained through interviews based on the PASE questionnaire and body composition measurements using the BIA Tanita.